Clarification of the Dissolution of Solid CaO and the Phosphorus‐Enrichment Capability of Calcium Silicates in the Multiphase Slag Based on the Ion and Molecule Coexistence Theory. Issue 2 (4th October 2017) - Xie, Senlin; Wang, Wanlin; Huang, Daoyuan; Li, Hongchao; Du, Yong
Abstract : Recently, a new refining method of using a solid/liquid coexistence multiphase slag for dephosphorization of hot metal was proposed, with the aim to improve the utilization efficiency of CaO and the degree of dephosphorization. Based on this method, an ion and molecule coexistence theory (IMCT) based the thermodynamic model has been developed to clarify the behavior of solid CaO dissolution and the phosphorus‐enrichment capability of calcium silicates in the multi‐phase slag in this article. According to the calculated mass action concentration of the related structural units, the reaction mechanism between solid CaO and the liquid slag in the multi‐phase slag is explained. Meanwhile, the phosphorus‐enrichment capability of calcium silicates is probed. The results show that the dissolution of solid CaO into the multi‐phase slag will be enhanced with the addition of the temperature or the increase of the FeO content, the mass percent ratio of FeO to Fe2 O3 (m(FeO)/m(Fe2 O3 )), and the P2 O5 content, while the high basicity (CaO/SiO2 ) will restrict the dissolution of solid CaO. Besides with the increase of basicity and m(FeO)/m(Fe2 O3 ), the phosphorus‐enrichment contribution ratio of 2CaO · SiO2 displays an exponential growth tendency, while it exhibits an asymmetric parabolic relationship with the increase of FeO, and it slightly decreases with the increase of P2 O5 and unchanged with the temperature. Those results obtained can provide a fundamental guidance for the dephosphorization by using the CaO‐based solid/liquid coexistence multiphase slag for hot metal treatment. Abstract : An ion and molecule coexistence theory based on the thermodynamic model has been developed in this article. According to the calculated mass action concentration of the related structural units, the reaction mechanism between solid CaO and the liquid slag in the multi‐phase slag is explained, and the phosphorus‐enrichment capability of calcium silicates is probed.